Band shifting and magnetic anisotropy switching induced by electric field in CrI3/1T′-MX2 heterojunction. (19th July 2021) - Wu, Zebin; Liu, Xin; Shen, Zhong; Xue, Yufei; Wu, Xiaoping; Zhong, Tingting; Wang, Jingjing; Pan, Jiaqi; Li, Chaorong; Song, Changsheng
Abstract: Manipulating magnetism by the electric field (EF) is a well-established technology that has been applied in two-dimensional materials systems. Here, based on first-principles calculations, we study the influence of the EF on the band structure and magnetic characteristics of the CrI3 /1T′-MX2 heterojunction. The results show amounts of charge exchange at the interface accompanying an obvious band shifting at the Γ point around the Fermi level. The magnetic moment of CrI3 /1T′-MX2 is visibly increased under an external EF relative to isolated CrI3 . Particularly, the magnetic anisotropy of CrI3 /1T′-MX2 switching from out-of-plane to in-plane can be modulated by the EF, while this change does not occur in isolated CrI3 . In addition, the topological properties of the heterojunction are still preserved by a nontrivial topological invariant Z 2 = 1. Our findings provide theoretical guidance for the spintronic application of CrI3 /1T′-MX2 materials.